Flow Cytometric Analysis of Cell Division by Dilution of CFSE and Related Dyes. Issue 1 (1st April 2013) - Lyons, A. Bruce; Blake, Stephen J.; Doherty, Kathleen V.
Abstract: The technique described in this unit uses the intracellular fluorescent label carboxyfluorescein diacetate succinimidyl ester (CFSE) to track proliferating cells. Covalently bound CFSE is divided equally between daughter cells, allowing discrimination of successive rounds of cell division. The technique is applicable to in vitro cell division, as well as to in vivo division of adoptively transferred cells and can resolve eight or more successive generations. CFSE is long lived, permitting analysis for several months after cell transfer, and has the same spectral characteristics as fluorescein, so monoclonal antibodies conjugated to phycoerythrin or other compatible fluorochromes may be used to immunophenotype the dividing cells. In addition, information is given on a second‐generation dye, Cell Trace Violet (CTV), excited by 405‐nm blue laser light. CTV is chemically related to CFSE, but allows the 488‐nm line of the Argon laser to be used for other probes. Curr. Protoc. Cytom . 64:9.11.1‐9.11.12. © 2013 by John Wiley & Sons, Inc.